miR-486-5p Restrains Extracellular Matrix Production and Oxidative Damage in Human Trabecular Meshwork Cells by Targeting TGF-β/SMAD2 Pathway - Le Xu; Yiming Zhang; Hua Long; Bo Zhou; Haibo Jiang (Journal of Ophthalmology)
Background. Glaucoma is characterized by elevated intraocular pressure caused by aqueous outflow dysfunction. Trabecular meshwork plays a key role in controlling intraocular pressure by modulating aqueous outflow. This study investigated the protective effects of miR-486-5p in H2O2-stimulated human trabecular meshwork cells (TMCs). Methods. TMCs were disposed with 300 μM H2O2 to establish oxidative damage models in vitro. miR-486-5p mimics and its controls were transfected into TMCs, and cell apoptosis and extracellular matrix production (ECM) genes were measured by flow cytometry, western blotting, and immunofluorescence staining. Activities of superoxide dismutase (SOD) and malondialdehyde (MDA) were also assayed. Online tools and luciferase reporter assays were used to uncover the relationship between miR-486-5p and the TGF-β/SMAD2 pathway. Results. We found that H2O2-induced oxidative damage in TMCs and miR-486-5p was downregulated in H2O2-stimulated TMCs. Overexpression of miR-486-5p mitigated H2O2-induced oxidative damage by inhibiting apoptosis, reducing cleaved caspase-3/9 expression, reducing MDA levels, and increasing SOD levels as well as downregulating ECM genes. SMAD2 was demonstrated to be targeted by miR-486-5p, and miR-486-5p inhibited TGF-β/SMAD2 signaling in H2O2-stimulated TMCs. Additionally, SMAD2 was upregulated by H2O2, and SMAD2 upregulation abrogated the protective effects of miR-486-5p against H2O2-induced injury. Conclusion. miR-486-5p restrains H2O2-induced oxidative damage in TMCs by targeting the TGF-β/SMAD2 pathway.